2008
DOI: 10.1097/qai.0b013e31816a1d4f
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic, Virologic, and Clinical Consequences of Episodes of Transient Viremia During Suppressive Combination Antiretroviral Therapy

Abstract: Episodes of low-level viremia are frequent and short lasting, and the low proportion of episodes with clinical events suggests that leaving therapy unchanged is a clinically acceptable strategy. In contrast, high-level viremia is associated with resistance and is often followed by therapy changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 17 publications
3
31
0
Order By: Relevance
“…A minority (6 to 9%) of patients with initial LLV progressed to higher degrees of viremia (4,5,(30)(31)(32). Thus, approximately 4% to 8% of the total population that achieved an initial pVL of Ͻ50 cpm in the studies subsequently developed persistent LLV of Ͻ500 cpm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A minority (6 to 9%) of patients with initial LLV progressed to higher degrees of viremia (4,5,(30)(31)(32). Thus, approximately 4% to 8% of the total population that achieved an initial pVL of Ͻ50 cpm in the studies subsequently developed persistent LLV of Ͻ500 cpm.…”
Section: Resultsmentioning
confidence: 99%
“…LLV is common during cART, although actual rates vary across studies (ranging from 18 to 34%) due to differences in study designs, population, and pVL assay used (4,5,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). Virtually all of these studies included viral blips, and only a few provided estimates of LLV persistence after viral suppression (4,5,30,32).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it has been found that the incidence of persistent low-level viremia is more frequent than high-level viremia when evaluating the virological response in subjects with HIV infection and HAART, reporting incidences of 29% and 6.7% for readings > 50 copies/mL and > 1,000 copies/mL, respectively (Van Sighem et al, 2008). Likewise, the UK-CHIC study reported that the cumulative risk for resistance mutation detection for two of the three primary classes of ARV therapy within a population increases in time, passing from 6% to 14% and 20% after a follow-up period of 2, 4, and 6 years for each period (Phillips et al, 2005).…”
mentioning
confidence: 99%
“…Despite durable suppression of viral replication, T-cell activation during times of illness or infection can cause bursts of HIV-1 replication activity in infected cells [94]. The clinical significance of these "blips" are currently not thought to be relevant [103]. However, it is possible that detectable viremia may be indicative of the acquisition of viral resistance [103].…”
Section: Hiv Infectionmentioning
confidence: 99%